Effect of boron and carbon addition on microstructure and mechanical properties of metastable beta titanium alloys. (15th February 2015) - Banoth, Ravinaik; Sarkar, Rajdeep; Bhattacharjee, Amit; Nandy, T.K.; Nageswara Rao, G.V.S.
Highlights: Effect of boron and carbon on properties of three beta titanium alloys studied. Ti–15V–3Cr–3Mo–3Sn, Ti–10V–2Fe–3Al, and Ti–5V–5Mo–5Al–3Cr alloys studied. Hardness and 0.2% YS increases and elongation to failure deteriorates with the B & C addition. Ageing in comparison to solution treatment results in increase in strength and decrease in elongation. Low ' n ′ values and multiple slopes are observed in log–log plots of true stress–true strain curves. Abstract: Effect of boron and carbon on microstructure and mechanical properties of β titanium alloys Ti–15V–3Cr–3Mo–3Sn, Ti–10V–2Fe–3Al, and Ti–5V–5Mo–5Al–3Cr has been studied in detail. The addition of boron and carbon results in refinement of β grain size and α-precipitates during ageing. While the hardness and tensile strength increase with the addition of boron and carbon, the elongation to failure deteriorates. The increase in strength is attributed to a synergistic effect of grain refinement and load sharing by TiB and TiC particles; whereas decrease in elongation is due to the brittleness of these hard particles. Ageing results in increase in strength and decrease in elongation as compared to solution treatment condition. In this case, the effect of boron and carbon is marginal. Further enhancement in the properties can be achieved by fine tuning heat treatment parameters. Multiple slopes are observed in log–log plots of true stress–true strain thereby implying different deformation mechanisms over a large range of plastic deformation.